La mediación de conflictos en la convivencia escolar. - Arias Chiguano, Elvia Margarita (2018)
The problems that are experienced daily in each of the homes influence the members of the family in such a way that they are reflected in the school, through the behaviors of the children, hindering the teaching-learning process, hindering communication and replacing it many times for aggressive and violent behavior. In this context education theorists identify as the main cause of conflicts in the classroom, the existence of a model of school organization still too rigid, inflexible and decontextualized from social and economic reality. This situation has a negative weight of influence among schoolchildren, causing discontent, boredom and demotivation, rejection of the school reality and its norms. From this perspective, it was considered urgent to diagnose a problem that has become common in the institutions of the educational system where, in the absence of the peaceful mediation of conflicts, it has generated difficulties in institutional school coexistence. The objective generated by the present research project was to describe the importance of conflict mediation as an educational action for the strengthening of the school coexistence of the children of the four years of Basic General Education of the Educational Unit "Provincial Council of Pichincha". The research had a quantitative approach, of a descriptive nature, it was supported in methods such as deduction, analysis; data collection techniques such as interview and survey were applied, through instruments such as the question guide and the questionnaire respectively. The results of the investigation reveal serious limitations of the classroom management of teachers for the mediation of conflicts; therefore, the importance of research is dimensioned in the recommendation of institutional management strategies that improve the remediation of conflicts and school coexistence.